Verstehen. De la ciencia a la cibernética - Garaventa, Carlos A. (2009)
This writing is aimed at approaching social sciences? methodology\nin an analytical manner. It presents a demarcation criterion to determine what can be deemed as science and what cannot, as well as the idea that the so-called\nsocial sciences are not sciences as such and that it is a mistake to expect them to\nbe so. An answer to the queries of what Law is and of whether there is or not a\nlegal science can also be found.\nFurther, this work intends to prove that in social cybernetics it is impossible to\nexplain or predict human conduct, which can just be understood. In addition, it is\na mistake to expect objectivity in the study thereof, not because of the fact of the\nobject of study being human beings but because the human beings carrying out\nthe study are immersed in the object of study. It is also impossible to establish\ngeneral or universal rules to govern social behavior.\nThis work provides an invitation to think about, to question and to doubt all\nwhich we have been imposed with as rigid during our entire lives; to accept that\nit is possible for somebody making a statement to make mistakes, as well as we\nourselves may make mistakes; to learn from such mistakes and, mainly, from our\nown mistakes. This writing does not unveil universal truths, it just ends where it\nbegins, accepting the possibility of being wrong